x-(-11)=17

Simple and best practice solution for x-(-11)=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(-11)=17 equation:


Simplifying
x + -1(-11) = 17

Multiply -1 * -11
x + 11 = 17

Reorder the terms:
11 + x = 17

Solving
11 + x = 17

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + x = 17 + -11

Combine like terms: 11 + -11 = 0
0 + x = 17 + -11
x = 17 + -11

Combine like terms: 17 + -11 = 6
x = 6

Simplifying
x = 6

See similar equations:

| y+4x-2=0 | | -6x-10=19-5x | | 13+x=-20 | | 3*4.5-y=9 | | 2x^2+3y^2+12x-12y-210=0 | | 7(2x+9)=3x+100 | | 6+3*5-2=18 | | 5(3x-6)=12 | | 19=23-2v | | -2(4x-2)+6x=4(x+3) | | 4m-9= | | 6+3*5-2=5 | | 2(3x+2)+6(2x-1)=40 | | 13x-4=2x+4 | | -72=-8(4-2x)-8(1-2x) | | 13x-4=2x+2 | | 2p=96-10 | | 5p-7p=3p+1 | | 13x+4=-5x+1 | | -86=-2(1-6a) | | 6sqrtx=x | | -5(-3v+5)-8v=3(v-5)-4 | | 13x+4=-5x-3 | | 2m+3m=4m-9 | | 4(2x-5)=43 | | -37=-3(1+6m)-2(m+7) | | 3m^3-15m^2+75m=0 | | x^2+y^2-22x+112=0 | | 2b-5b=-9 | | (2x-1)/4+(3x+4)/8=(1-4x)/12 | | 3(z+3)=2(z+8) | | 31=5x+5x-9 |

Equations solver categories